KEHIDUPAN SOSIAL EKONOMI PEKERJA PERKEBUNAN KELAPA SAWIT PTPN IV KEBUN TIMUR AFDELING III DI KECAMATAN BATAHAN, KABUPATEN MANDAILING NATAL ( 2006–2024) - Dela Rizana; Meri Erawati; Felia Siska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the establishment of PTPN IV Kebun Timur Afdeling III in Batahan District, Mandailing Natal Regency, and examine the socio-economic changes experienced by its workers during 2006–2024. The research employed the historical method, consisting of heuristics, source criticism, interpretation, and historiography. Data were collected through company archives, field observations, interviews with management and workers, and supported by secondary sources, including books, journals, and statistics from the Central Bureau of Statistics. The findings indicate that the acquisition of PT Andalas Agro Nusantara in 2006 marked the beginning of PTPN IV Kebun Timur's development, creating employment opportunities and improving workers' welfare. Socio-economic changes were reflected in higher income, better housing conditions, improved access to education and healthcare, and increased asset ownership. However, workers' welfare remained influenced by employment status, with permanent employees receiving better facilities and social security than contract and daily workers.